2016
DOI: 10.1080/21541264.2015.1127315
|View full text |Cite
|
Sign up to set email alerts
|

Insights into centromeric transcription in mitosis

Abstract: The major role of RNA polymerase II (RNAP II) is to generate mRNAs. I recently uncovered a novel function of RNAP II in chromosome segregation in mitosis, installing the cohesin protector, Shugoshin, at centromeres. Here I will discuss the current understanding of RNAP II-dependent centromeric transcription in mitosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…As expected, melatonin treatment via oral administration substantially restored the spindle/chromosome structural defects to promote the meiotic progression, suggesting that melatonin indeed has the potential to ameliorate the oocyte quality. Because kinetochore attaches chromosomes to spindle microtubules and maintains the attachment to growing or disassembling microtubules to drive chromosome segregation, spindle/chromosome abnormalities are always accompanied by the errors of kinetochore‐microtubule attachments . We further determined the effect of melatonin on the stability of kinetochore‐microtubule attachments in BPA‐exposed oocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, melatonin treatment via oral administration substantially restored the spindle/chromosome structural defects to promote the meiotic progression, suggesting that melatonin indeed has the potential to ameliorate the oocyte quality. Because kinetochore attaches chromosomes to spindle microtubules and maintains the attachment to growing or disassembling microtubules to drive chromosome segregation, spindle/chromosome abnormalities are always accompanied by the errors of kinetochore‐microtubule attachments . We further determined the effect of melatonin on the stability of kinetochore‐microtubule attachments in BPA‐exposed oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Because kinetochore attaches chromosomes to spindle microtubules and maintains the attachment to growing or disassembling microtubules to drive chromosome segregation, 49,50 spindle/chromosome abnormalities are always accompanied by the errors of kinetochore-microtubule attachments. 17,51,52 We further determined the effect of melatonin on the stability of kinetochore-microtubule attachments in BPA-exposed oocytes. Our findings showed that melatonin significantly elevated proportion of stable kinetochoremicrotubule attachments in BPA-exposed oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…congression (46,49). Therefore, spindle and chromosome abnormalities are always accompanied by errors in kinetochore-microtubule attachments (50)(51)(52). We then assessed the stability of kinetochore-microtubule attachments after cool treatment that depolymerizes microtubules that are unattached to kinetochores.…”
Section: Discussionmentioning
confidence: 99%
“…This was due to the occurrence of defective spindle assembly and chromosome alignment. Because spindle/chromosome abnormalities are always caused by the error of kinetochore-microtubule attachment [28,29], we further assessed it to show that a large number of free kinetochores which were not attached by the microtubules were present in HU-exposed oocytes, leading to misaligned chromosomes. Therefore, these observations suggest that the nuclear maturation of oocytes is impaired upon HU exposure.…”
Section: Agingmentioning
confidence: 99%